20 Years of the Agile Manifesto: on Agile Project Management - Pacagnella Junior, Antonio Carlos; da Silva, Vinicius Romeiro (Management and Production Engineering Review, 2023)
Agile Project Management is a topic that has become popular both in business and academia, since the publication of the Agile Manifesto – a historic landmark in this subject. In the next 20 years, there was a relevant scientific production that must be analyzed to provoke reflection about the knowledge built up in this period. In this sense, this study aims to analyze the relevant scientific literature on Agile Project Management through a systematic review and a bibliometric analysis of articles published in scientific journals with Digital Object Identifier, in English, from the Web of Science and Scopus databases, from 2001 to 2021. The research results enable us to gain insights into the characteristics of this knowledge domain, regarding its volume and evolutionary trend, main contributors (i.e. scientific journals, authors, and their affiliations), main studies, methods used, and its central thematic axes.
Keywords: Agile project management; Systematic review; bibliometric analysis; PRISMA; Literaturereview